Keberhasilan Pola Komunikasi Organisasi UPNTV dalam Membangun Stakeholders - Aulia Azzahra, Farah; Hidayatullah, Khuurin Iin Islami; Wildan, Muhammad; Pamungkas, Dimas Tri Agung; Prabarani, Theodora Zaviena; Zuhri, Saifuddin (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
In this research, the author discusses how an organization’s communication effectively manages relationships with stakeholders to achieve long-term success. In this research, the author will dig deeper into how widely UPNTV is known to audiences outside the communication science study program, how UPNTV’s strategy is to maintain a positive image in the eyes of stakeholders, and what strategic steps are taken to continue to improve branding, and how UPNTV’s vertical or horizontal communication with external parties helps improve the existence and quality of the programs produced. This research uses a qualitative method with a communication ethnography study as its research design. The data collection techniques that will be used in this research are participant observation and in-depth interviews. Overall, UPNTV has succeeded in building a good existence and reputation outside the Communication Studies Program. This is proven by the many requests for cooperation from external parties both in the form of streaming services and program cooperation.